Influence of Perfluorooctane Liquids in the Formation of Sticky Silicone Oil - Hirotsugu Takashina; Akira Watanabe; Tadashi Nakano (Journal of Ophthalmology)
Purpose. To examine the influence of perfluorooctane (PFO) in the formation of sticky silicone oil (SO). Methods. We performed in vitro experiments using PFO, SO, aqua, and canola oil (CO). The surface tension of CO relative to aqua is very close to that of SO or PFO. First, each material (0.5 ml) was carefully injected into the bottom of a transparent container that was filled with either aqua or CO. Next, a second material (0.5 ml) with a specific gravity that was lower than that of the first material was carefully injected onto the first material. Results. When the first material was injected into the container, the shape of the aqua was found to be close to a sphere, while the shapes of SO or PFO were prolate spheroids. Subsequently, when the second material was injected onto the first material, SO and CO completely adhered to the PFO, with the created immiscible droplets exhibiting a smooth surface. However, aqua did not create any immiscible droplets due to absence of adhesion to PFO or SO. Conclusions. Sticky SO is composed of PFO and SO, which easily form an immiscible droplet due to the low interfacial tension.